PERANCANGAN APLIKASI KEAMANAN UNTUK MEMBATASI HAK AKSES USER BERBASIS WINDOWS - Mendarissan Aritonang (Universitas Methodist Indonesia, 2016)
Windows operating system security system was needed to the things that are not expected, like perubahan configurations and settings on the Windows operating system that can automatically change the windows registry values can be fatal in windows operating system. Security applications for Microsoft Windows designed to make it easier for administrators to lock the windows and some functions of the executable file. This application can hide the drives are seen as critical data storage Microsoft windows security applications for this tool is designed by using Borland Delphi Programming